Obesity and Pregnancy in Saudi Women - Othman, Mohammad; Himayda, Samah S; Shaaban, Lamia (Archives of Clinical and Medical Case Reports, 2018)
Objective: To determine the effect of obesity on pregnancy compared to non-obese pregnant Saudi women. Methodology: This is a prospective cohort research conducted over seven months in Jeddah Maternity and Children Hospital (MCH), Jeddah, Saudi Arabia. Sample included pregnant women with single fetus and cephalic presentation came to the booking clinic. Participants were classified into five groups depending on their BMI according to WHO criteria as underweight, normal weight, overweight, obese & morbidly obese. SPSS was used with p-value of< 0.05 to calculate statistical significance. Results: The frequency of abortion, postdated pregnancy and Caesarean section were higher in obese women compared to non-obese women. Conclusion: Obese women pregnancy is a high risk for pregnancy and labor complications. It is advisable to achieve normal BMI before conception.